9(-6-27)=x

Simple and best practice solution for 9(-6-27)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(-6-27)=x equation:


Simplifying
9(-6 + -27) = x

Combine like terms: -6 + -27 = -33
9(-33) = x

Multiply 9 * -33
-297 = x

Solving
-297 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-297 + -1x = x + -1x

Combine like terms: x + -1x = 0
-297 + -1x = 0

Add '297' to each side of the equation.
-297 + 297 + -1x = 0 + 297

Combine like terms: -297 + 297 = 0
0 + -1x = 0 + 297
-1x = 0 + 297

Combine like terms: 0 + 297 = 297
-1x = 297

Divide each side by '-1'.
x = -297

Simplifying
x = -297

See similar equations:

| x+x+548615=1129455 | | 5.5x=-60.5 | | 5u+4=6 | | -3(7p-7)=-84 | | X/4/9=36/7 | | 2+4=a-2 | | 3k+4=ak-2 | | 3(z-4)-4=4(z-8) | | 3lx+6l=36 | | f(x)=X*2+2x-5 | | 6(x-4)=-4(x+2)+28 | | 5x^2+2y^2=0 | | x^2-.81=0 | | 162+7m=281 | | f(x)=cosx/x^2 | | 36x^2-12x^6+x^10+5x=150 | | (X-2)+(X-3)=1 | | -2+10k=38 | | N+15=-10 | | 24n-144=288 | | 8+6x-10x=15-8x | | 84-7m=140 | | 84-7m=148 | | 12x+2y= 88 | | 15+n=17-1 | | 4(x-5)=72/6 | | 23-x=87 | | 7/9x-5=5 | | 286=2w^2-4w | | 6(3x-2)=114 | | M+25=10 | | 0.9x+6.4=25.3 |

Equations solver categories